Eukaryotic ribosome biogenesis at a glance - Thomson, Emma; Ferreira-Cerca, Sébastien; Hurt, Ed (Journal of cell science, 2013)
Ribosomes play a pivotal role in the molecular life of every cell. Moreover, synthesis of ribosomes is one of the most energetically demanding of all cellular processes. In eukaryotic cells, ribosome biogenesis requires the coordinated activity of all three RNA polymerases and the orchestrated work of many (>200) transiently associated ribosome assembly factors. The biogenesis of ribosomes is a tightly regulated activity and it is inextricably linked to other fundamental cellular processes, including growth and cell division. Furthermore, recent studies have demonstrated that defects in ribosome biogenesis are associated with several hereditary diseases. In this Cell Science at a Glance article and the accompanying poster, we summarise the current knowledge on eukaryotic ribosome biogenesis, with an emphasis on the yeast model system.